2019
DOI: 10.28991/cej-2019-03091269
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Drivers’ Affectability and Satisfaction with Black Spots Warning Application

Abstract: Since a significant percentage of crashes occur at black spots, different methods have been proposed to prioritize the modification of these spots and prevent crashes. One of these prevention methods in transportation is the hazard warning systems. The purpose of this study is to evaluate the satisfaction of drivers and their affectability from a map-based warning application is evaluated. To this end, black spots were identified on one of the two-way two-lane highways in the North-West of Iran and 32 male dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…-The Frobenius norm of the matrix includes only the analog precoding, analog combining, and channel matrix while there is no need for data estimation. -Under the same conditions, our analytical and simulation findings show that proposed precoding achieves better spectral efficiency than other existing hybrids such as the ZF precoding [27], the MMSE precoding [21,28], and the Kalman precoding [26].…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…-The Frobenius norm of the matrix includes only the analog precoding, analog combining, and channel matrix while there is no need for data estimation. -Under the same conditions, our analytical and simulation findings show that proposed precoding achieves better spectral efficiency than other existing hybrids such as the ZF precoding [27], the MMSE precoding [21,28], and the Kalman precoding [26].…”
Section: Introductionmentioning
confidence: 70%
“…In [26], the authors designed a circuit to enhance gain and reduced power consumption used in different wireless systems. The authors in [27] offered a Black Spots Warning Application that reduces crashes at black spots.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that the difference between warning and non-warning in the black spots was marked with a confidence level of 95% effective warning in reducing the speed of the black spots. Most drivers are very satisfied with the warning using car speakers [28].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Where Ps is the transmitting power of source S, h is channel gain of S-D1 link and nD1 denoted the additive white Gaussian noise (AWGN) at D1 which has zero-mean and variance N0. b1 and b2 are power allocation coefficients for data symbols x1 and x2 that is wished to send from; S toD1 and D2, respectively and satisfied 21 12…”
Section: Energy Harvesting Phasementioning
confidence: 99%